Classification and comparison of physical and chemical properties of corn stalk from three regions in China - Lu, Wang; Ronghou, Liu; Chen, Sun; Wenfei, Cai; Yiwe, Tao; Renzhan, Yin; Yuanfei, Mei (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: Corn stalk samples from Anhui, Jiangxi and Shanghai were used as test materials. Their physical, chemical and thermo-chemical engineering characteristics were analyzed. The similarities and differences in properties of corn stalk from the three regions were determined using SIMCA-P and SPSS software in order to obtain a proper energy utilization method of corn stalk. The results show that the corn stalk from Shanghai has significant differences from the samples of Jiangxi and Anhui. In particular, the following properties of corn stalk from Shanghai such as the contents of cellulose, calcium (Ca), iron (Fe), crude ash, volatile matter, carbon (C), nitrogen (N), and oxygen (O) are significantly different from those of Jiangxi and Anhui samples (P smaller than 0.05). While other properties such as the contents of magnesium (Mg), copper (Cu), zinc (Zn), moisture, hydrogen (H), and sulfur (S) have no significant difference among samples of three regions. Compared with the corn stalk in Anhui and Jiangxi, the Shanghai samples are more suitable for the production of ethanol because of their higher ratio of cellulose to hemi-cellulose content. Because of its high content of ash and low calorific value, the Shanghai corn stalk is suitable for the gasification process instead of for direct combustion or bio-oil production. The research can provide a reference for raw material selection for biomass energy production and utilization. Keywords: corn stalk, physical and chemical properties, bioenergy, principal components analysis, partial least squares discriminant analysis DOI: 10.3965/j.ijabe.20140706.012 Citation: Wang L, Liu R H, Sun C, Cai W F, Tao Y W, Yin R Z, et al. Classification and comparison of physical and chemical properties of corn stalk from three regions in China. Int J Agric & Biol Eng, 2014; 7(6): 98－106.